2010
DOI: 10.1021/bi100556m
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Steady State Kinetic Studies of the Fidelity of Nucleotide Incorporation by Yeast DNA Polymerase δ

Abstract: Eukaryotic DNA polymerase delta (pol δ) is a member of the B family of polymerases and synthesizes most of the lagging strand during DNA replication. Yeast pol δ is a heterotrimer comprised of three subunits: the catalytic subunit (Pol3) and two accessory subunits (Pol31 and Pol32). Although it is one of the major eukaryotic replicative polymerase, the mechanism by which it incorporates nucleotides is unknown. Here we report both steady state and pre-steady state kinetic studies of the fidelity of pol δ. We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 61 publications
3
42
1
Order By: Relevance
“…It was previously reported that yeast Pol ␦ has an apparent k pol of about 1 s Ϫ1 for the chemical step, which is too slow, considering that the fork movement has been estimated to be ϳ100 nucleotides s Ϫ1 (51,52 (15,31). The k pol and K d dTTP of Pol ⑀ are also similar to k pol values reported for other polymerases, such as T4, T7, and RB69 gp43 (33,40,53) (Table 5).…”
supporting
confidence: 68%
“…It was previously reported that yeast Pol ␦ has an apparent k pol of about 1 s Ϫ1 for the chemical step, which is too slow, considering that the fork movement has been estimated to be ϳ100 nucleotides s Ϫ1 (51,52 (15,31). The k pol and K d dTTP of Pol ⑀ are also similar to k pol values reported for other polymerases, such as T4, T7, and RB69 gp43 (33,40,53) (Table 5).…”
supporting
confidence: 68%
“…Indeed, the discrimination between correct and incorrect nucleotides may already be quite efficient without dedicated proofreading mechanisms. By explicitly taking into account the dependence of the rates on the concentrations of nucleotides and pyrophosphate, the theory provides direct comparison with experimental observations [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. In particular, the theory explains the Michaelis-Menten dependence of the mean growth velocity on the nucleotide concentration, which is a basic feature of enzymatic kinetics.…”
Section: Discussionmentioning
confidence: 98%
“…Although the first assumption is not supported by experimental observations [19], it is often considered because of its great simplicity. The second assumption captures the observation that the polymerization rate constants k (13) take similar values within the set of correct (respectively incorrect) pairings [13,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. According to these assumptions, the model only needs the four rate constants k p ±c and k p ±i for polymerization and depolymerization, together with the two Michaelis-Menten constants K c and K i for correct and incorrect pairings.…”
Section: Bernoulli-chain Modelmentioning
confidence: 99%
“…Pol ε displays a similarly high rate of DNA synthesis (115). However, dNTP levels in the cell are far below the K m values for these enzymes (4, 116). When measured at physiological dNTP levels, and in the presence of competing rNTPs, DNA synthesis proceeds at ~50 nt/sec, which is commensurate with rates of fork movement in the cell (117).…”
Section: Lagging Strand Replicationmentioning
confidence: 94%